1988
DOI: 10.1002/bms.1200150308
|View full text |Cite
|
Sign up to set email alerts
|

A mass spectral study of cyclophosphamide concerning a thermally induced rearrangement reaction

Abstract: The electron impact mass spectra of cyclophosphamide (1) are very sensitive towards experimental conditions in view of the kind of sample handling, the type of mass spectrometer used and the temperature of evaporation. The reason for this phenomenon is the elimination of HCl from the molecular ion by a specific 1,5-hydrogen transfer yielding an ion at m/z 224 which is structurally related to the bicyclic compound 4 with its typical fragment ions at m/z 175 and 147. Thermal excitation of the sample increases th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…, or, if they are present, they have very low RA s. In the linear and angular isoquinoline derivatives, the ionization occurs on the aromatic moiety (Scheme ). Compounds 8 ( n = 2, R  N(CH 2 CH 2 Cl) 2 ) behaved as expected on the basis of the earlier findings,7, 8, 22–24 with the exception that the cyclophosphamide derivatives discussed here exhibited relatively abundant M + . ( 8a : m/z 315/317 RA = 17/11% and 8b : 8/5%) ions and very weak [M–CH 2 Cl] + ( 8a : m/z 266/268, RA = 2/0.7% and 8b : 0.7/0.1%) ions.…”
Section: Resultssupporting
confidence: 85%
“…, or, if they are present, they have very low RA s. In the linear and angular isoquinoline derivatives, the ionization occurs on the aromatic moiety (Scheme ). Compounds 8 ( n = 2, R  N(CH 2 CH 2 Cl) 2 ) behaved as expected on the basis of the earlier findings,7, 8, 22–24 with the exception that the cyclophosphamide derivatives discussed here exhibited relatively abundant M + . ( 8a : m/z 315/317 RA = 17/11% and 8b : 8/5%) ions and very weak [M–CH 2 Cl] + ( 8a : m/z 266/268, RA = 2/0.7% and 8b : 0.7/0.1%) ions.…”
Section: Resultssupporting
confidence: 85%
“…In addition to the common primary fragments already discussed, compounds 14 – 17 (as reported earlier for cyclophosphamide and its derivatives3, 15, 16 and their 3,1,2‐O,N,P analogs1) gave the ions [M–CH 2 Cl] + , [M–HClCH 2 Cl] + and [M–HCl] + . with variable abundances (Table 4), the first of these often being the most abundant; this is comparable with the situation for the 1,4,4a,5,6,7,8,8a‐2 H ‐3,1,2‐benzoxazaphosphinine 2‐oxides, which practically did not give the second ion at all 1.…”
Section: Resultsmentioning
confidence: 57%
“…The molecular ion was seldom observed due to the presence of the N‐mustard. Busker et al 6. studied the fragmentations of CP under EI conditions, and found that the initial fragment ion at m/z 224 was formed by 1,5‐elimination of HCl followed by loss of chloromethylene to generate the most abundant fragment ion at m/z 175.…”
mentioning
confidence: 99%